Transición energética en Alemania e integración de fuentes de energías no convencionales (2019)
German energy policy has undoubtedly been a worldwide benchmark for renewable energy. With the implementation of the Renewable Energy Sources Act in 2000, 36% of gross electricity consumption in 2018 came from renewable sources. In addition, greenhouse gas emissions fell by 328 million tonnes between 1990 and 2016. However, this has also increased the cost of stabilizing the grid, reaching a new record of 1.4 billion euros in 2017 and the price to the final consumer increased substantially, being one of the highest in the European Union. However, it has already been reducing, as it has reduced the cost of new technologies. Even so, the consensus of society is that these extra costs are worth paying. Therefore, it is important to know the energy transition program that Germany has experienced and its effects, which is the objective of this paper.